Maintenance of Light Standards, a Case-Study - Rommert Dekker; J. Robert van der Meer; Raymond Ph. Plasmeijer; Ralph E. Wildeman; Jacco J. de Bruin (Tinbergen Institute, 1996)
This paper discusses several strategies for the maintenance of light standards, where each light standard consists of n independent and identical lamps screwed on a chandelier. The lamps are subject to stochastic failures, and must be correctively replaced if the number of failed lamps reaches a prespecified number m; a norm that is set by the local management to guarantee a minimumluminance. As lamps have an increasing failure rate, and there is a fixed cost of hoisting the chandelier, we propose various variants of the m-failure group replacement rule which have in particular an age-criterion to indicate which of the non-failed lamps must be preventively replaced at the time that the chandelier is lowered for a corrective lamp replacement; we show how the optimalthreshold age can be determined. It appears that this modification reduces the long run average maintenance cost of the Europe Combined Terminals with approximately 8.3%.
Keywords: 330; Instandhaltung; Ersatzinvestition; Theorie